Can Parameterizations Reproduce the Gravity Wave Momentum Fluxes and Drag Simulated by a Global High‐Resolution Model? - I. Toghraei; F. Lott; L. Köhler; C. C. Stephan; M. J. Alexander (Geophysical Research Letters)
Abstract We compare the gravity wave (GW) parameterizations used in the IPSLCM6 climate model with the GWs resolved in the ICON global model with 5 km horizontal resolution. The parameterizations are run offline using ICON fields coarse‐grained to a 100 km grid and compared to the GWs with smaller scales that are resolved in ICON. Overall, the drags are comparable, the momentum fluxes align well, and each GW parameterization (fronts, convection, and mountains) plays a role at geographical locations consistent with ICON. Among the differences, we find that in ICON, GWs are substantially attenuated above the subtropical jets; this is underestimated by the parameterizations. It also seems that, in this comparison, ICON underestimates frontal waves in the mid‐latitudes, that the parameterizations underestimate the convective waves in the tropics, and that the mountain waves are more alike.